2017
DOI: 10.1002/tea.21407
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of inquiry materials to explain complexity of chemical reasoning in physical chemistry students’ argumentation

Abstract: One aim of inquiry activities in science education is to promote students’ participation in the practices used to build scientific knowledge by providing opportunities to engage in scientific discourse. However, many factors influence the actual outcomes and effect on students’ learning when using inquiry materials. In this study, discourse from two physical chemistry classrooms using the Process‐Oriented Guided Inquiry Learning (POGIL) approach was analyzed using a lens of scientific argumentation. Analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 52 publications
1
41
0
Order By: Relevance
“…One reason explaining these results was that the experimental group students participated in the various inquiry‐based instructions and games in the OGSA. As reported by previous studies, inquiry‐based and innovative instructions support the development of positive attitudes toward science (Barab & Dede, ; Chen et al, ; Lindgren et al, ; Maxmen, ), deeper knowledge understanding, and the use of language and arguments like those used by scientists (Golanics & Nussbaum, ; Hasancebi & Gunel, ; Meluso et al, ; Moon et al, ). Specifically, the students in the three experimental groups were allowed to explore information collaboratively, test their ideas with experiments, make observations, take photos and videos for reflection, and communicate their ideas during the OGSA participation.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…One reason explaining these results was that the experimental group students participated in the various inquiry‐based instructions and games in the OGSA. As reported by previous studies, inquiry‐based and innovative instructions support the development of positive attitudes toward science (Barab & Dede, ; Chen et al, ; Lindgren et al, ; Maxmen, ), deeper knowledge understanding, and the use of language and arguments like those used by scientists (Golanics & Nussbaum, ; Hasancebi & Gunel, ; Meluso et al, ; Moon et al, ). Specifically, the students in the three experimental groups were allowed to explore information collaboratively, test their ideas with experiments, make observations, take photos and videos for reflection, and communicate their ideas during the OGSA participation.…”
Section: Discussionsupporting
confidence: 52%
“…The teaching of argumentation, in which students need to build arguments by considering evidence and counter evidence, using appropriate reasoning, and evaluating alternative standpoints, has become increasingly prevalent and also an essential goal for science education (Duschl, Schweingruber, & Shouse, ; Moon, Stanford, Cole, & Towns, ; Osborne et al, ). It has been reported that argumentation is rarely found in the science discourse of most students, because regular classroom discourse typically follows a pattern in which the teacher initiates discussion by using a question with a known answer, the students respond to the question, and then the teacher evaluates the students' responses (Driver, Newton, & Osborne, ; Kilinc, Demiral, & Kartal, ; Lemke, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…">2.Modeling practices in evolution (Lehrer & Schauble, ) 3.Chemical reasoning in constructing arguments in thermodynamics (Moon, Courtney, Cole, & Towns, ) 4.Model‐based inquiry (Hernandez, Couso, & Pintó, )…”
Section: Resultsmentioning
confidence: 99%
“…Studies on argumentative discourses and model-based reasoning are scarce; findings suggest that most students do not express uncertainty in the explanations or justifications they give for their models. The effect is increased when the task includes noisy data (Buck, Lee & Flores, 2014), or promotes important conceptual advances to understand a hydrological phenomenon, but with large variations amongst classrooms if a central curriculum does not integrate the activities (Zangori, Vo, Forbes & Schwarz, 2017), or the complexity of the model that guides the reasoning of students and the cognitive demand of the task are related to the type of tests included in their arguments (Moon, Stanford, Cole & Towns, 2017). These research results are valuable since they provide an understanding on how science instruction can drift away from a traditional, teacher-centric approach towards a student-centric approach that regards them as active participants of their own learning.…”
Section: Palabras Clavementioning
confidence: 99%